Are There Jobs in Academic Pulmonary Medicine in Canada? A Resident’s View of the Future - Jae Yang; Charles K Chan (Canadian Respiratory Journal)
A survey of all Canadian academic institutions with an adult pulmonary training program was undertaken in 1992 to investigate the number of positions in pulmonary medicine that would be available up to 1997. The positions were divided into clinician scientist (75% research) and clinician teacher (75% clinical) categories. Inquiry into specific areas of interests and prerequisite training requirements were made. Ten of 14 centres responded; 35 to 44 positions were identified, 22 to 27 for clinician scientists with at least two to four years’ research training after completion of a clinical pulmonary fellowship. For the remaining 13 to 17 clinician teacher positions, the requirement was for two to three years of additional clinical training beyond the clinical pulmonary fellowship. Some centres did not specify whether available positions were in the clinician scientist or in the clinician teacher group. The results of the survey suggest that there are jobs available in academic pulmonary medicine but that they are mainly in the basic research area, requiring at least an MSc, and preferably a PhD or equivalent research training. A questionnaire is included in an attempt to obtain information about other opportunities in both academic and community hospitals.